Profil Laten Gejala Depresi Pada Remaja Indonesia: Temuan dari Indonesia Family Life Survey 5 (IFLS-5) - Novrianto, Riangga; Sari, Fina Herlina (ANIMA Indonesian Psychological Journal, 2025)
Adolescent depression is a major public health issue, yet there is limited study on depressive symptoms among Indonesian adolescents. Identifying distinct subgroups within this population could help inform targeted prevention and intervention efforts. This study analyzed data from the Indonesia Family Life Survey 5 (IFLS-5) utilizing Latent Profile Analysis (LPA) to identify depressive symptom subgroups. Chi-Square Tests were utilized for univariate analysis, and Logistic Regression Analysis examined associated factors. Among 2,267 adolescents, two symptom profiles emerged: (1) “Low-Level” Depressive Symptoms Profile (73.31%); and (2) “High-Level” Depressive Symptoms Profile (26.69%). Sex or gender was the only significant factor in the univariate analysis, with Logistic Regression Analysis revealing that female adolescents were more likely to exhibit high levels of depressive symptoms. These findings suggest that female adolescents are at greater risk for more severe depressive symptoms, highlighting the need for targeted prevention and intervention strategies.